Effects of post-silking low temperature on the starch and protein metabolism, endogenous hormone contents, and quality of grains in waxy maize - Guo, Jian; Qu, Lingling; Wei, Qi; Lu, Dalei (Frontiers in Plant Science, 2022)
Waxy maize has many excellent characteristics in food and manufacturing industries. However, post-silking low temperature (LT) has severe limitations on its grain yield and quality. In this study, field and pot trials were conducted to investigate the effects of LT during the grain-filling stage on the physiological, biochemical, and functional characteristics of two waxy maize grains. The field and pot trials were performed with sowing date and artificial climate chamber, respectively, for LT treatment from post-silking to maturity. Results in pot trial were used to explain and validate the findings in field trial. Compared with the ambient treatment, the LT treatment significantly reduced kernel weight during the grain filling stage (P < 0.05). LT treatment in both environments resulted in an average decrease in dry weight of SYN5 and YN7 at maturity by 36.6% and 42.8%, respectively. Enzymatic activities related to starch and protein biosynthesis decreased under the LT treatment during the filling stage, accompanied by a decrease in the accumulation amounts and contents of soluble sugar and starch, and a decrease in protein accumulation amount. Meanwhile, the contents of abscisic acid, indole-3-acetic acid, and gibberellin 3 in grains decreased under the LT treatment during the filling stage. Peak, through, breakdown, final, setback, and pasting viscosities of grains decreased after LT treatment. LT treatment decreased the gelatinization enthalpy of grains and increased the retrogradation percentage. In conclusion, post-silking LT stress altered the content of grain components by inhibiting the production of phytohormones and down-regulating the enzymatic activities involved in starch and protein metabolism, which resulted in the deterioration of grain pasting and thermal properties.